Title in English: Wars and the decline of democracy - benaouda, dalila; gaid, salima (Journal of Social Sciences and Humanities, 2025)
The world is facing radical changes at the level of political regimes whereby democracy seems to shrink infront of liberalism , populisme and other political regims .Historians , economists and politicians alike argue whether the essence of democracy is constent or has changed whith the change in economic interests. Warfare is considered as a recurrent historical phenomenon , it is characterized as being permanent and unchangeable in terms of repercussions. Warfare is a state of frequent war and peace , it was and is still considered as a major and principal tool in international affairs and global relations. Therefore, nations have used this tool to arrive at achieving their national interests. So , warfare is a mere extension of politics and political agendas with a variety in the tools used to accomplish certain aims whether peacefully or with a deliberate use of military force. Politics is therefore a soft power and or a peaceful dispute or conflict. The wars which are deeply traced in politics are based on a variety of political choices towards territorial and international issues as on a variety in interests and expressing them. This latter leads us to discuss the relation between conflicts and democracy as long as the world wars which took place in the last centuries were all justified by certain discourse. Democratic forces , capitalism and liberalism had all justified many wars in the name of democracy and so all attempts to impose democracy is a mere colonial system in disguise. To cut a long story , all countries no matter how devloped they are tend to see democracy as the most coveted system of ruling , however this latter has altered in its essence due to the rapid change in the economic world order , therefore democracy becomes a guilded concept to hide imperial and colonial interests